IMPLEMENTASI KEBIJAKAN TUNJANGAN KINERJA PEGAWAI DI LINGKUNGAN KEMENTERIAN PERTANIAN (STUDI DI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN SULAWESI UTARA) - PAPUNAS, NURFITRI; Rompas, Welson; Tulusan, Femmy (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This research moved from the initial observation that the Employee Performance BenefitsPolicy Implementation in the Agriculture Technology Assessment Unit in North Sulawesi indicated noteffective enough because encountered some conditions that indicate problems in implementation. Thepurpose of this study was to determine how the Employee Performance Benefits Policy Implementation inAgriculture Technology Assessment Unit in North Sulawesi.Research using qualitative methods.The informants as many as 10 employees. Collecting data withinterview techniques; while the data analysis using analytical techniques interactive model of Miles andHubermann. Implementation of the model that is used in this research is the theory of policy implementationof Van Metter and VanHorn.The results of this study demonstrate policy implementation performance benefits of employees inNorth Sulawesi in general has been quite good but needs to be improved, namely (1) the human dimension:the lack of supervision to be the cause of corruption time employees. (2) Dimensions implementing Attitude:There is still tolerable attitude of the parties has taken the performance benefits so that employees whoviolate the rules spared from cuts. (3) Dimensions organization communication between implementers, lackof communication with other parties regarding appropriate intake BPTP periodic reports causing delays inthe disbursement of performance benefits.Referring to some of the findings in this study it is necessary to give somesuggestions as solutionsto problems, as follows: (1) it is necessary to increase the security guard or officer who recorded employeeout during office hours, it is important for improving employee discipline. (2) Regulations or provisionsconcerning the calculation of the performance benefits cuts should be done properly and consistently withtougher sanctions. In order for the parties that deal cutting performance benefits can work consistently andfirmly, so that employees who violate the rules will not be spared from cuts. (3) In need of facilities / specialapplications in support of coordination andcommunication between the Ministry of Agriculture.Keywords: policy implementation, performance benefits